Women as Imagery Consumer (Clothes and Cosmetics as the Phenomena of Cultural Perspective of Postmodernism) - Srinarwati, Dwi Retnani (Universitas Muhammadiyah Surakarta, 2015)
The problems of woman as imagery consumer are closely related to consumer’s culture. The contemporary culture of consumer causes a condition which forces people to use consumer goods to symbolize different and various lifestyles. That who she is, what class she comes from, and how she consumes are things which make others realize that identity is not fixed, but it is something that can be played, constructed, and reconstructed. Almost every day, people are attacked with imagery of ideal woman which is constructed through and by media. That woman should perform enchantingly in public places, recently, becomes the core theme for advertisement of popular media, particularly woman’s media. Fashion and cosmetics reveal the clearest arena for consumer’s passion. This leads some women to an endless beauty hunting in the cycle of satisfaction seeking which then enable them to join the world of loneliness and alienation. The recent phenomenon indicated that cyber space through internetwhich can across space and time can function as body imagery media. Finally, on the one hand, woman becomes consumer for fulfilling their ideal standard; on the other hand, the industry of beauty and body treatment which has become big business, has brought ‘woman as imagery consumer’.